Faecalcrobiota metabolites: emerging insights into cancer radiotherapy outcomes - Gao, Yuzhuo; Zeng, Baozhao; Wang, Zhicheng; Liang, Shuo; Yang, Yanming (Frontiers in Microbiology, 2025)
The connection between gut microbiota and the onset, progression, and management of cancer is receiving increasing attention. Gut microbiota metabolites serve as crucial mediators that influence the cancer process by modulating immune responses and metabolic pathways. Research has shown that these metabolites significantly affect cancer development, prognosis and therapy. For example, the effectiveness and side effects of radiotherapy are closely linked to the metabolites produced by gut microbiota. Radiotherapy can disrupt the balance of gut microbiota, increase intestinal permeability, and trigger inflammatory responses, all of which may lead to adverse reactions such as damage to the intestinal mucosa and a compromised anti-cancer effect. This review emphasizes the role of gut microbiota metabolites in tumor formation and progression by affecting signaling pathways and the tumor immune microenvironment. It explores how these metabolites can influence the efficacy and side effects of radiotherapy and discusses innovative cancer treatment strategies that leverage gut microbiota metabolites. By integrating recent preclinical and clinical findings, the review proposes that incorporating colony modulation therapies into cancer treatment could enhance therapeutic strategies and provide patients with safer and more effective options.